Studies on dinoflagellates in the northern Baltic Sea - Hällfors, Heidi (Helsingin yliopisto, 2013)
Dinoflagellates are an important part of the Baltic Sea phytoplankton community. The group includes significant primary producers, consumers, bloom-forming species, toxic species, and species capable of rapid expansion to new areas. The aim of this thesis is to provide new information on the occurrence of dinoflagellates in the northern Baltic proper and the western Gulf of Finland by investigating 1) trends in temporal and spatial distribution of dinoflagellates, 2) patterns of co-occurring taxa in the dinoflagellate community, and 3) external factors that explain dinoflagellate occurrence. These issues were investigated in four studies, on which this thesis is based. In the first study, we compared the phytoplankton communities of the early 1900s and the present, and examined the role of dinoflagellates in the species compositions of these two periods. In the second study, the focal point was moved forward in time to the annual and interannual dynamics and diversity of the present-day dinoflagellate community, and in the third study further to a more detailed level, the description of a new taxon, Heterocapsa arctica subsp. frigida, and its ecology and distribution. Lastly, in the fourth study we shifted focus from seasonal, interannual and geographical occurrence to smaller-scale occurrence, i.e. the vertical distribution of dinoflagellates in the water column, as represented by a case study on Dinophysis acuminata and D. norvegica. A total of 47 dinoflagellate species, 28 genera, and four higher-level taxa were observed. Of the species-level taxa, 15 have not been previously reported from the northern Baltic proper and/or the Gulf of Finland. We also contributed to the knowledge of Baltic Sea dinoflagellate diversity by formally describing the new taxon, Heterocapsa arctica subsp. frigida, which furthermore represents a for phytoplankton unusual taxonomical level, i.e. a subspecies. The conspecificity of H. arctica subsp. frigida with H. arctica subsp. arctica, described from the Canadian Arctic, was ...